Unfolded : Paper in Design, Art, Architecture and Industry. - Schmidt, Petra (De Gruyter, 2009)
In Unfolded-Paper in Design, Art, Architecture and Industry paper conquers the third dimension and demonstrates the undreamed-of possibilities it holds today for lightweight construction, product design, fashion and art. From "Paper", the collection of bags by Stefan Diez, to Konstantin Grcic's paper models and the scented paper garments of Issey Miyake, this book presents paper as a high-quality contemporary and ecological material. An enormous selection of projects, the lavish design and numerous illustrations provide designers with invaluable inspiration for their work. The content core of the book is a comprehensive list of state-of-the-art paper products and innovative paper technologies, supporting designers in their everyday work with detailed information on the "high-tech" material paper. From Japanese washi paper and paper foam, to ceramic paper and carbon fiber paper, Unfolded presents the latest in research and development, as well as the most important methods and technologies in handcrafts and industry.